THE INFLUENCE OF GOVERNMENT APPARATUS COMPETENCE AND E-GOVERNMENT POLICY IMPLEMENTATION ON IMPROVING PUBLIC SERVICES AT DEPARTMENT OF POPULATION AND CIVIL REGISTRATION AMBON - Amin, Mohamad (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
The purpose of this study was to determine the effect of government competence and the implementation of e-government policies on the quality of public services at Ambon Population and Civil Registration Office. The research method used in this research is quantitative. The populations in this research were employees at Ambon City Population and Civil Registration Office with a total of 30 people. The sample measurement technique uses a saturated sampling technique, which used all the population as the samples. The data collection technique used in this research is a questionnaire. The data analysis is using multiple linear regressions with SPSS 23 application. The results showed that the competence of government apparatus has a significant effect on the quality of public services, the implementation of e-government policies has a significant effect on the quality of public services, and the competence of government apparatus and e-government policies can be used as predictors of increasing or turning the public services quality.